Efficiency of Removing Xylene Vapor from Air Utilizing Nano Graphene and Nano Graphene Oxide - Akram Tabrizi; Mostafa Jafarizaveh; Hamid Shirkhanloo; Farideh Golbabaeie (بهداشت و ایمنی کار)
Introduction: Volatile organic compounds (VOCs) are hazardous toxic pollutants in the air, which are released from various industrial sources. Due to the adverse effects of xylene on health, the effective removal of VOCs from the air by nano sorbents is crucial. In this study, nanographene (NG) and nanographene oxide (NGO) were used as adsorbents to investigate the efficiency of xylene removal. Material and Methods: In this study, in order to investigate the absorption efficiency of nanographene and nanographene oxide after the synthesis of nano absorbents in a dynamic system, xylene vapor was produced in a chamber in pure air and stored in a Tedlar sampling bag and then transferred to the adsorbent. Subsequently, the effect of various parameters such as xylene concentration, inlet air flow rate, and absorbent mass values at 32% humidity and 25°C temperature on the absorption rate and performance of the desired absorbents was investigated. Finally, the gas chromatographic flame ion detector (GC-FID) determined the concentration of xylene in air after the adsorption-desorption process. Results: The average adsorption efficiencies for NG and NGO were found to be 96.8% and 17.5%, respectively. The characteristics of the NG and NGO adsorbents indicated that the particle size range was less than 100 nanometers. Conclusion: The results demonstrated that the adsorption efficiency of NG for the removal of xylene from the air is higher than that of NGO. The GC-MS method validated the proposed approach in real air samples.